The Effectiveness of Local Wisdom-Based Teaching Materials in Enhancing Creative Writing Skills of Elementary School Students - Santosa, Agus Budi; Basuki, Yudi; Puspita, Ari Metalin Ika (Journal of English Language Teaching and Linguistics, 2019)
This study aims at describing the effectiveness of local wisdom-based teaching materials on the creative writing skills of elementary school students. The sample of the study was 2nd-grade students at SDN 1 Campurdarat, which amounted to 45 students. The research design uses quasi-experimental research in the form of a nonrandomized control group pretest-posttest design. The data were collected using the instrument of creative writing skills. The analysis was performed by different tests using the Wilcoxon formula. The results showed that there were differences before and after the use of teaching materials based on local wisdom towards students' creative writing skills. The results of evaluating creative writing on each learning from learning 1 to 6 show the students' mastery in achieving creative writing criteria.